KOLEKTOR SURYA PRISMATIK - Philip Kristanto; James Laeyadi (Institute of Research and Community Outreach, Petra Christian University, 2000)
Solar collector is the essential item of equipment which transforms solar radiation energy to some other useful energy form, for example as the water heater. One of the shape solar collector, is prismatic which have ability to receive solar radiation intensity from all the sun's position, so that using solar energy as water heater can more effective. Solar collector can absorb solar radiation intensity and convert it to useful calor for heating the water inside the pipes of the collector, so the temperature of the water is rise and natural convection is happen by the basic of thermosiphon because effect of mass density fluid difference. From the experiment is found the best position to locate the collector which can produce optimal efficiency are 15 degrre from east to north. Abstract in Bahasa Indonesia : Kolektor surya merupakan suatu bagian dari peralatan yang dibutuhkan untuk mengubah energi radiasi matahari ke bentuk energi panas untuk berbagai keperluan, misalnya sebagai pemanas air. Salah satu bentuk dari kolektor surya adalah bentuk prisma yang memiliki kemampuan untuk menerima intensitas radiasi matahari dari segala posisi matahari, sehingga diharapkan pemanfaatan energi tersebut sebagai pemanas air dapat lebih efektif. Kolektor surya akan menyerap energi dari radiasi matahari dan mengkonversikannya menjadi panas yang berguna untuk memanaskan air di dalam pipa-pipa kolektor, sehingga suhu air akan meningkat dan terjadi konveksi alami berdasarkan efek termosipon karena adanya perbedaan masa jenis fluida. Dari percobaan didapatkan bahwa posisi terbaik dari kolektor yang menghasilkan efisiensi yang optimal dengan menempatkan kolektor 15° dari arah timur ke utara. Kata kunci: Pemanas air tenaga surya